Skeletal muscle shape influences joint torque exertion through the mechanical advantages - Umehara, J.; Taniguchi, M.; Yagi, M.; Li, G.; Soufi, M.; Otake, Y.; Sato, Y.; Fukumoto, Y.; Yamagata, M.; Nakai, R.; Ichihashi, N. (Journal of Applied Physiology, 2025)
Skeletal muscle morphology is linked to its function. Extensive literature demonstrates that muscle volume is crucial for determining joint torque exertion, a primary function of muscle. However, whether muscle shape also influences torque exertion capacity remains unclear. This study illustrates that the three-dimensional shape of muscles independently determines joint torque exertion, irrespective of muscle volume, using a statistical shape model designed to quantify muscle shape features. The statistical shape model was developed from magnetic resonance images of the quadriceps femoris muscles in 33 healthy young adults (26 ± 5 yr; 18 males). We investigated the association between the shape components of each quadriceps femoris head and isometric knee extensor torque. The findings reveal that the mediolateral curvatures of the rectus femoris (R2 = 0.60) and the bulging in the distal region of the vastus medialis (R2 = 0.65) were associated with increased knee extensor torque despite muscle volumes. Moreover, the rectus femoris and vastus medialis shapes were correlated with the medial-directed line-of-action (r = -0.42 and p = -0.36). The vastus medialis shape was correlated with the moment arm of the patellar lateral spin (p = 0.45). Therefore, the three-dimensional muscle shape determines the joint torque exertion by forming the mechanical advantages that balance the force/torque output optimally. Our findings demonstrate that muscle shape is crucial in the mechanical output of skeletal muscle and provides a framework for enhancing the understanding of muscle morphology and its functionality.